2002
DOI: 10.1002/fld.402
|View full text |Cite
|
Sign up to set email alerts
|

Performance of finite volume solutions to the shallow water equations with shock‐capturing schemes

Abstract: SUMMARYNumerical methods have become well established as tools for solving problems in hydraulic engineering. In recent years the ÿnite volume method (FVM) with shock capturing capabilities has come to the fore because of its suitability for modelling a variety of types of ow; subcritical and supercritical; steady and unsteady; continuous and discontinuous and its ability to handle complex topography easily.This paper is an assessment and comparison of the performance of ÿnite volume solutions to the shallow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 38 publications
3
56
0
Order By: Relevance
“…To compare with the numerical results given in [28] where numerical tests of shallow water equations by several well-established Riemann solvers are reported, we ran again the test with a 41×41 mesh and give the profiles of h, u and v on the cross-section of x = 92.5 m in Figure 11. It is observed that the present model has competitive numerical accuracy in simulating 2D bore shock wave.…”
Section: D Partial Dam-break Problemmentioning
confidence: 99%
“…To compare with the numerical results given in [28] where numerical tests of shallow water equations by several well-established Riemann solvers are reported, we ran again the test with a 41×41 mesh and give the profiles of h, u and v on the cross-section of x = 92.5 m in Figure 11. It is observed that the present model has competitive numerical accuracy in simulating 2D bore shock wave.…”
Section: D Partial Dam-break Problemmentioning
confidence: 99%
“…FVMs of second-order accuracy for shallow water model based on flux-vector splitting and fluxdifference splitting were reported in Anastasiuo and Chan [2], Burguete and Navarro [7], Lin et al [23] and Brufau et al [6]. Erduran et al [11] evaluated and reviewed some existing approximate Riemann solvers for shallow water equations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the implementation of explicit schemes is much easier than that of implicit schemes, explicit schemes require careful time step selection in order to fulfill the stability requirement. The semicoupled algorithm in this study is calculated under the maximum allowable time steps used in the work of Erduran et al (2002). The local time stepping for the temporal discretization is achieved using the fifth stage Runge-Kutta scheme.…”
Section: Boundary Conditionsmentioning
confidence: 99%